Advances in Transportation Engineering Select Proceedings of TRACE 2018 - Pulugurtha, Srinivas; Ghosh, Indrajit; Biswas, Sabyasachi (Lecture Notes in Civil Engineering,, 2019)
This book comprises select papers presented at the International Conference on Trends and Recent Advances in Civil Engineering (TRACE 2018). The book covers cutting-edge methods and applications in the field of traffic control, transportation planning, road maintenance, and highway and pavement engineering. Case studies on traffic safety, pedestrian behavior, and highway maintenance and design are also presented in this book. The contents of this book are useful for researchers and practitioners working in transportation and traffic engineering. .